Gambaran Hand Hygiene Menggunakan Sabun Antiseptik Dan Hand Sanitizer Terhadap Jumlah Kumah Dalam Pencegahan Penularan Covid-19 - Anik Enikmawati; Sulastri Sulastri (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Covid-19 is currently still worrying because an event that is reported in all geographic areas of Indonesia and the emergence of this virus is pathogenic. Transmission of this virus from person to person is mainly caused by droplets from coughing or sneezing, personal contact such as touching and shaking hands, touching objects or surfaces with the virus on them, then touching the mouth, nose, or eyes before washing hands. Hand, in this case, are a source of transmission of the Covid-19 virus, so proper hand hygiene practices can reduce the spread of transmission. This study aims to describe the number of germs on hands to wash hands with running water using soap and wash hands using hand sanitizer. Research Methods: this type of descriptive qualitative research. Data were collected by post-test two-group design and laboratory tests. This study uses two treatments, namely handwashing treatment with soap and water and hand washing medicines using hand sanitizer. Results: Observations from bacterial inoculation showed that respondents who were given handwashing treatment using running water and soap, the average picture of the number of germs on the agar medium were 7.6 colonies, while respondents who were given handwashing treatment using a hand sanitizer were the number of germs. which grew on agar media an average of 18.9 colonies. Conclusion: the average picture of the number of germs from bacterial inoculation on hands that have been washed using running water using soap and washing hands using hand sanitizer is the most germs that grow on hands using hand sanitizers compared to washing hands using water and soap.